The Impact of Green Development of Industrial Parks on the Reduction of Carbon Emissions in Urban Areas—Empirical Research on Green Industrial Parks in China - Xiang Yu; Wentao Hu; Mudan Wang (Earth's Future)
Abstract China has over 2,500 national and provincial industrial parks, stimulating the economics growth, meanwhile being the primary sources of carbon dioxide emissions and other pollutants. Assessing the mechanisms and impacts of the policies of pilot programs of green industrial parks on urban carbon emissions offers critical insights into the efficacy and application of green and low‐carbon development. This study utilizes a staggered difference‐in‐differences model to examine the impact of green industrial park pilot policies. The results demonstrate that green industrial parks have effectively reduced carbon emissions of the studied counties in terms of total and intensity. The economic scales and the administrative levels of any given city significantly influence the implementation effect of green industrial park policy. In applying the green industrial park policy, reducing the carbon emissions is more pronounced in cities with larger economic scales and higher administrative levels. Environmental regulation policies and green industrial park pilot policies exhibit a certain degree of substitution effect. The green industrial parks drive urban carbon emission reduction through three main channels: enhancing green technologies, optimizing industrial structures, and elevating economic agglomeration levels. Overall, this study provides a new perspective, a methodological reference, and empirical evidence for promoting green and low‐carbon development for industrial parks in the different regions and developing countries.